Peanut shells derived solid acid catalyst for biodiesel production - Pua F.-L.; Tan C.-Y.; Dang W.-H.; Palanisamy K. (Asian Research Publishing Network, 2023)
Waste peanut shells are contributed to a large quantity of lignocellulosic waste. This project was aimed to utilize the waste materials for a better benefit. Waste peanut shells, were used as raw material to prepare a new solid catalyst for biodiesel production. Solid acid catalyst derived from waste peanut shells was used to catalyze the esterification process in biodiesel production from waste cooking oil. Solid acid catalyst was prepared by in-situ impregnation with sulfuric acid. This new catalyst was used to catalyze the esterification of high free fatty acid (FFA) value waste cooking oils as pretreatment step prior biodiesel production. The effects of catalyst loading, oil-to-methanol molar ratio and catalyst reusability on the catalytic activity were investigated. The highest catalytic activity with 71.58% esterification rate was achieved and it can be reused for three times under optimized condition. The catalyst can be easily separated for reuse compared with homogenous catalyst which used in biodiesel production. Waste peanut shells are potential to be converted into useful feedstock and the derived catalyst can replace traditional liquid acid catalyst in biodiesel production especially for high acid value content feedstock. 2006-2015 Asian Research Publishing Network (ARPN).